Risk Factors Related to Decreased Vision in Primary School Children in Palembang - Dicky Hartono (Department of Opthalmology, Faculty of Medicine, Universitas Sriwijaya, 2021)
Introduction. Visual acuity is the ability of the eye to see an object clearly, and this depends on the ability of the eye to accommodate. Myopia is one of the causes of a sharp decline in vision in children aged 8-12 years. Close working distance is one of the most frequently mentioned risk factors for myopia. Head and back posture that bends forward when reading or doing other close-up tasks causes a higher prevalence of myopia. This study was conducted to describe risk factors related to decreased vision in elementary school children. Methods. The study was a descriptive research with a sample of 100 elementary school children taken by simple random sampling. Data was taken using a questionnaire and a Snellen chart. Results. A total of 100 students participated in this study. Most of the participants were aged 11 years old. Based on visual acuity, 20 students have decreased right eye vision, and 21% have decreased left eye vision. Most respondents read every day for 1 hour time as many as 58 (58%) people and had screen time for less than 2 hours (52%). In addition, based on family history, most respondents had parents' glasses (73%). Conclusion. More elementary school children had normal right and left eye vision than those with decreased vision. Most respondents have less screen time and less reading duration.